Process control of ore crushing using block-oriented predictive model - Михайленко, Олексій Юрійович (Technology audit and production reserves, 2015)
The problem of developing a system of predictive ore crushing control is considered. A method of forming forecasting control of ore crushing, which is based on static nonlinearities inverting input-output of block-oriented model and approximation of trajectories of control systems of orthonormal Laguerre functions, allowing reduce the problem of determining the sequence of actions to control the problem of quadratic programming. By means of simulation it is found that the proposed system provides higher quality control of transients and calculated load on the control unit as compared to non-linear predictive control. Using the proposed system will improve the efficiency of ore dressing in mining enterprises through the formation and stabilization of the required granulate characteristics of crush ore, which will reduce energy consumption in the next stages of processing, and as a result, reduce the cost of the final product.